Measuring Sound at a Cold-Water Coral Reef to Assess the Impact of COVID-19 on Noise Pollution - De Clippele, Laurence H.; Risch, Denise (Frontiers in Marine Science, 2021)
This study compares the noise levels at the cold-water coral Tisler reef, before and after the closure of the border between Norway and Sweden, which occurred as a direct result of the COVID-19 pandemic. The Tisler reef is a marine protected area located under a ferry 'highway' that connects Norway and Sweden. Cold-water coral reefs are recognised as being important hotspots of both biodiversity and biomass, they function as breeding and nursing grounds for commercially important fish and are essential in providing ecosystem functions. Whilst studies have shown that fishery, ocean warming, and acidification threaten them, the effects of noise pollution on cold-water coral reefs remains unstudied. To study the severity of noise pollution at the Tisler reef, a long-term acoustic recorder was deployed from 19 January 2020 until 26 May 2020. From 15 March COVID-19 lockdown measures stopped passenger vessel traffic between Norway and Sweden. This study found that the overall noise levels were significantly lower after border closure, due to reduced ferry traffic, wind speeds and sea level height. When comparing the median hourly noise levels of before versus after border closure, this study measured a significant reduction in the 63-125 Hz 1/3 octave band noise levels of 8.94 ± 0.88 (MAD) dB during the day (07:00:00-19:59:59) and 1.94 ± 0.11 (MAD) dB during the night (20:00:00-06:59:59). Since there was no ferry traffic during the night, the drop in noise levels at night was likely driven by seasonal changes, i.e. the reduction in wind speed and sea level height when transitioning from winter to spring. Taking into account this seasonal effect, it can be deduced that the COVID-19 border closure reduced the noise levels in the 63-125 Hz 1/3 octave bands at the Tisler reef by 7.0 ± 0.99 (MAD) dB during the day. While the contribution of, and changes in biological, weather-related and geophysical sound sources remain to be assessed in more detail, understanding the extent of anthropogenic noise pollution at the Tisler cold-water coral reef is critical to guide effective management to ensure the long-term health and conservation of its ecosystem functions.